Spalt mediates an evolutionarily conserved switch to fibrillar muscle fate in insects - Schönbauer, C; Distler, Jutta; Jährling, N; Radolf, M; Dodt, HU; Frasch, Manfred; Schnorrer, Frank (Nature, 2011)
Flying insects oscillate their wings at high frequencies of up to 1,000 Hz(1,2) and produce large mechanical forces of 80 W per kilogram of muscle(3). They utilize a pair of perpendicularly oriented indirect flight muscles that contain fibrillar, stretch-activated myofibres. In contrast, all other, more slowly contracting, insect body muscles have a tubular muscle morphology(4). Here we identify the transcription factor Spalt major (Salm) as a master regulator of fibrillar flight muscle fate in Drosophila. salm is necessary and sufficient to induce fibrillar muscle fate. salm switches the entire transcriptional program from tubular to fibrillar fate by regulating the expression and splicing of key sarcomeric components specific to each muscle type. Spalt function is conserved in insects evolutionarily separated by 280 million years. We propose that Spalt proteins switch myofibres from tubular to fibrillar fate during development, a function potentially conserved in the vertebrate heart-a stretch-activated muscle sharing features with insect flight muscle.